Evaluating the Impact of Developer Experience on Code Quality: A Systematic Literature Review - Lopes, Jefferson G. M.; Oliveira, Johnatan; Figueiredo, Eduardo (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2024.28446, 2024)
The relationship between developer experience and code quality continues to provoke extensive debate and diverging interpretations in software engineering. To investigate this subject, we conducted a systematic literature review and identified 18 relevant papers from which we aim to answer an overarching research question: to what extent does developer experience impact on code quality? Our analysis reveals different definitions and dimensions for both developer experience and code quality, highlighting the complexity and multifaceted nature of their relationship. We also observed contradictory results on the impact of developer experience on code quality. This literature review contributes in two key ways. First, it synthesizes various perspectives on developer experience and code quality, offering a consolidated viewpoint of the current academic work. Second, it uncovers significant gaps in our understanding of the relationship between these two concepts, pinpointing areas for further research and emphasizing the needs for more focused studies to bridge these knowledge gaps.